"Bisakah Kita tetap Memberi, walau Tak Suci?" Suatu Tinjauan Spiritualitas dalam Lirik Lagu Hindia-Membasuh sebagai Kemasan Budaya Populer - Situmorang , Sari Asi (JURNAL DIAKONIA, 2024)
This review discusses the style of spirituality contained in popular culture packaging through the lyrics of an Indian song entitled “Membasuh”. This research uses a qualitative approach with semiotic analysis. The findings of this review are the concept of leadership spirituality expressed through Jesus. This can be seen from the emphasis that humans live to give to each other. The concept of giving in the lyrics of this song also invites the general public to keep giving even though they consider themselves not holy. More than that, every listener is invited to open themselves as a space that gives forgiveness and loves others without worrying about past mistakes that make themselves trapped in a dark space.